Pengaruh Kesesuaian Sistem Pengendalian Intern, Sistem Kompensasi, dan Ketaatan Aturan Akuntansi terhadap Perilaku Tidak Etis dan Kecenderungan Kecurangan Akuntansi serta Akibatnya terhadap Akuntabilitas Kinerja pada Perguruan Tinggi Katolik di Indonesia - Laksmi, Vita Valentina Diah Ayu; Handayani, Dwi; Immanuela, Intan (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2017)
The tendency of accounting fraud (TAF) is characterized by actions and policies deliberately hide facts or do not provide real information for the purpose of deceiving or manipulation. This research was conducted in Catholic State Univesity in Indonesia listed in APTIK Directory 2012, using survey and questionnaire as instrument. Considering that this is a behavioral research, the unit analysis on this study is the officials and other staff that are responsible as budget user, accounting administrator, and the compiler of accountability report in the state Universities. Of the 95questionaires sent, there are 52 pieces of the back, it means the response rate achieved 54%. This results of this study show that variable intern control system, compensation system, and compliance with rules effect on unethical behavior. Internal control compliance, compensation system, compliance with rules, and unethical behavior effect on tendency of accounting fraud. Tendency of accounting fraud did not effect on performance accountability